Sources of return in the index futures markets - Adam Zaremba (Contemporary Economics, 2011)
The paper concerns an issue of existence of a risk premium in equity and index futures markets. The paper consists of four parts. The first part describes the basic hypotheses of forward curves in the futures market. In the second section, I formulate 5 hypotheses concerning a risk premium in the equity futures market, its forecastability, and its dependence on a market segment and development stage. The third part includes an empirical study, which confirms the existence of timedependent and partially predictable risk premium. The research was based on the Polish futures market in the years 2000-2010. The last section of the paper discusses potential implications for the financial market practice and indicates areas for further research.
Keywords: G13; G14; G17; 330; futures; risk premium; forward curve